2003
DOI: 10.1590/s0102-695x2003000300016
|View full text |Cite
|
Sign up to set email alerts
|

Constituintes apolares do fruto do açaí (Euterpe oleracea M. - Arecaceae)

Abstract: Revista Brasileira de Farmacognosia 2003a 90%, em 50 minutos], fluxo de 1 ml por minuto e detecção no UV, em comprimento de onda de 210 nm. Os cromatogramas das amostras foram comparados pelo tempo de retenção dos picos. Referências AbstractEuterpe oleracea M. (açaí) is an economically important palm found in many places throughout Brazil. The heart of palm is a well known delicacy all around the world while the fruit of this palm is eaten only in Brazil. This study deals with the chemical composition of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 1 publication
0
6
0
3
Order By: Relevance
“…No chemical differences were observed regarding fatty acid compositions when these three extracts were analysed (Mantovani, Fernandes & Menezes, 2003). There was a predominance of the unsaturated forms, including mostly: oleic acid (45.1%, 45.7%, 45.5% for pericarp, endocarp and whole fruit, respectively), followed by palmitoleic acid to a lesser extent (4.2 %, 4.8%, 4.3% for pericarp, endocarp and whole fruit, respectively).…”
Section: Inácio Lima Lopes Pessoa and Teixeiramentioning
confidence: 86%
“…No chemical differences were observed regarding fatty acid compositions when these three extracts were analysed (Mantovani, Fernandes & Menezes, 2003). There was a predominance of the unsaturated forms, including mostly: oleic acid (45.1%, 45.7%, 45.5% for pericarp, endocarp and whole fruit, respectively), followed by palmitoleic acid to a lesser extent (4.2 %, 4.8%, 4.3% for pericarp, endocarp and whole fruit, respectively).…”
Section: Inácio Lima Lopes Pessoa and Teixeiramentioning
confidence: 86%
“…Unsaturated fatty acids are also present in the "açaí" berry, with oleic acid being the major compound, and palmitic acid as a second major compound (Mantovani et al, 2003;Schauss et al, 2006). Schauss et al (2006) evaluated the "açaí" in powdered form and observed an inhibitory effect in the cyclooxygenase enzyme of type 1 and 2 in in vitro assays, concluding that "açaí" is a promising anti-inflammatory agent.…”
Section: Introductionmentioning
confidence: 99%
“…These substances showed a cardioprotective effect in rats improving the lipid profile (Bhattacharya et al, 2006). Another study reported a vasodilator effect on mesenteric vessels of rats related to a lipid profile improved by the açai fruit extract (Mantovani et al, 2003;Xie et al, 2011) reported the atheroprotective effects of açai fruit pulp in apolipoprotein E-deficient in mice, mediated by a reducing lipid peroxidation through boosting antioxidant enzymes and inhibiting pro-inflammatory cytokine production.…”
Section: Assays In Cardiovascular Diseasesmentioning
confidence: 98%